Model Pendidikan Rumah Tahfidz: Studi Rumah Tahfidz Abu Bakar Ash-Shidiq Bandung - Herdiansyah, Hendi (TARBIYAH: Jurnal Pendidikan Islam, 2024)
This study aims to describe in depth the education model of Rumah Tahfidz Abubakar Ash-Shidiq Bandung through fact-finding about the education system applied. This qualitative research uses literature and field study methods with data collection techniques through interviews, observations, literature studies and documentation studies. The results showed that the educational model of Rumah Tahfidz Al-Qur'an Abu Bakar Ash-Shiddiq Bandung applies a special approach that focuses on strengthening the memorization of the Qur'an, understanding and instilling Islamic values. The learning process is carried out using the intensive muraja'ah method, imitating the reading style of Sheikh Mishary Rashid Al-Afasy. This educational model has unique characteristics characterized by an emphasis on several key components, such as an integrated curriculum, a flexible learning structure, and qualified teachers and management that focuses on the well-being of teachers and the smooth operation of learning. This education model shows the institution's efforts to ensure accessibility and optimal quality of education for all students.